Flavonoids from Tetracera indica Merr. inhibit adipocyte differentiation and exert glucose uptake activities in 3T3-L1 adipocyte cells - Ahmed, Qamar Uddin; Hasan, Mohd Mehmudul; Sarian, Murni Nazira; Mat So'ad, Siti Zaiton; Bakhtiar, M. Taher; Latip, Jalifah (2016)
Tetracera indica Merr.(Family: DILLENIACEAE) is a large, woody, rain forest climber of Malaysia which is commonly known as Mempelas paya or sand paper plant. Two flavonoids MHQ-1 (wogonin) and MHQ-2 (norwogonin) were isolated from the stems ethanol extract of T. indica. Moreover, MHQ-1 and MHQ-2 including rosiglitazone as positive control were subjected to fluorescence glucose uptake test by 2-NBDG (fluorescent glucose analog) on mature adipocytes. Wogonin was found to show more cytotoxicity (IC50 <25 µg/mL) in comparison to norwogonin (no IC50 upto100 µg/mL) in MTT viability assay on 3T3-L1 preadipocyte cells. Structure activity relationships (SAR) study of both the flavonoids revealed that the methoxy (O-Me) substitution (wogonin) at position 8 of ring A of flavone skeleton is essential for inducing cytotoxicity on 3T3-L1 Pre-adipocytes. However, hydroxyl (OH) group at the same position (norwogonin) is safe to the cells (percent viability is above 80% for all the doses evaluated). Additionally, both the compounds were introduced to the cells in different safe concentrations as well as in different adipogenic cocktails. The adipogenic cocktails were modified by the compounds and rosiglitazone in the presence or absence of insulin. The results of adipogenesis showed that MHQ-1 and MHQ-2 induced adipogenesis like insulin and enhanced adipogenesis like rosiglitazone significantly in three different concentrations. Furthermore, both the compound stimulated the 2-NBDG uptake on mature adipocytes significantly. Results further confirm the traditional use of T. indica in the management of diabetes in Malaysia.